2015
DOI: 10.3748/wjg.v21.i3.997
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative trans-jugular porto-systemic shunt for oncological gastric surgery in a cirrhotic patient

Abstract: Abdominal surgery in cirrhotic patients with portal hypertension is associated with high incidence of disease and mortality. In these patients, oncological gastric procedures with lymph-nodes dissection show much higher complication rates than in normotensive portal vein patients. Thus, normalization of portal vein pressure may be a favorable determinant factor to reduce complications. We report a case of a patient with hepatitis C virus-related hepatic cirrhosis, esophageal varices, portal hypertension and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…A total of 8 original studies were identified. These included two case reports from the UK [ 5 ] and Italy [ 6 ], three case series from the USA [ 7 ], Spain [ 8 ] and France [ 9 ], and three retrospective studies from the USA [ 10 , 11 ] and Canada [ 12 ]. A retrospective study from the USA described 25 patients with cirrhosis undergoing abdominal or cardiothoracic surgeries [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 8 original studies were identified. These included two case reports from the UK [ 5 ] and Italy [ 6 ], three case series from the USA [ 7 ], Spain [ 8 ] and France [ 9 ], and three retrospective studies from the USA [ 10 , 11 ] and Canada [ 12 ]. A retrospective study from the USA described 25 patients with cirrhosis undergoing abdominal or cardiothoracic surgeries [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The etiology of liver cirrhosis was alcohol in 47.6% (10/21) of patients, hepatitis C in 28.6% (6/21), a combination of alcohol and hepatitis C in 9.5% (2/21), primary biliary cirrhosis in 9.5% (2/21), and cryptogenic in 4.8% (1/21) of patients [ 5 - 9 , 11 ]. Vinet et al reported 61.1% (11/18) of patients to have a non-alcohol etiology without any further specification [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In regards to preoperative TIPS before abdominal surgery, experience remains limited. To our knowledge this approach has been described in 7 prior studies [4,6,9,10,11,12,13] . The first study to describe this in 2001 included seven cirrhotic patients requiring planned extrahepatic intra-abdominal operations in which a "two-step"strategy" was applied performing TIPS in a time period ranging between 1-5 months prior to the planned procedure.…”
Section: Discussionmentioning
confidence: 99%